Guanine nucleotide exchange factor -H1 promotes inflammatory cytokine production and intracellular mycobacterial elimination in macrophages. Issue 18 (17th September 2017) - Wang, Hui; Wang, Jinli; Yang, Jiahui; Yang, Xiaofan; He, Jianchun; Wang, Ruining; Liu, Sudong; Zhou, Lin; Ma, Li
ABSTRACT: Mycobacterium tuberculosis ( M.tb ), which causes tuberculosis, is a host-adapted intracellular pathogen that can live within macrophages owning to its ability to arrest phagolysosome biogenesis. The guanine nucleotide exchange factor H1 (GEF-H1) may contribute to the phagocytosis of bacteria by macrophages through mediating the crosstalk between microtubules and the actin cytoskeleton. Its role in Shigella infection has been determined but little is known about the role of GEF-H1 in mycobacterial infection. In the present study, we demonstrated that GEF-H1 functioned as a key regulator of the macrophage-mediated anti-mycobacterial response. We found that both mRNA and protein expression levels of GEF-H1 were significantly upregulated in macrophage during mycobacterial infection. Moreover, silencing of GEF-H1 with specific siRNAs reduced the phosphorylation of p38 mitogen-activated protein kinase and TANK binding kinase 1 as well as the expression of interleukin-1β (IL-1β), IL-6, and interferon-β (IFN-β), without affecting nitric oxide production or autophagy. Importantly, GEF-H1 depletion attenuated macrophages-mediated mycobacterial phagocytosis and elimination. Taken together, our data supported that GEF-H1 was a novel regulator of inflammatory cytokine production and mycobacterial elimination, and may serve as a novel potential target for clinical treatment of tuberculosis.